The role of parietal cortex in the formation of color and motion based concepts - Cheadle, Samuel W.; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
Imaging evidence shows that separate subdivisions of parietal cortex, in and around the intraparietal sulcus (IPS), are engaged when stimuli are grouped according to colour and to motion (Zeki and Stutters 2013). Since grouping is an essential step in the formation of concepts, we wanted to learn whether parietal cortex is also engaged in the formation of concepts according to these two attributes. Using functional magnetic resonance imaging (fMRI), and choosing the recognition of concept-based colour or motion stimuli as our paradigm, we found that there was strong concept-related activity in and around the intraparietal sulcus (IPS), a region whose homologue in the macaque monkey is known to receive direct but segregated anatomical inputs from V4 and V5. Parietal activity related to colour concepts was juxtaposed but did not overlap with activity related to motion concepts, thus emphasizing the continuation of the segregation of colour and motion into the conceptual system. Concurrent retinotopic mapping experiments showed that within the parietal cortex, concept-related activity increases within later stage IPS areas.